Bridging Welfare and Work: Assessing Intensive Job Placement for Minimum Income Recipients - Yarine Fawaz; Laura Hospido; Júlia Martí Llobet (Institute of Labor Economics (IZA), 2025)
We evaluate the effects of a randomized activation program targeting recipients of the Spain's national Minimum Income Scheme. The intervention combined personalized coaching, job-search assistance, soft-skills training, and, in one treatment arm, also digital-skills workshops. While short-run employment effects were limited, the program significantly reduced the prevalence of informal work and improved participants' financial resilience. Gains were particularly pronounced among those who received the digital-skills component, who reported large improvements in digital task performance. Half a year after receiving the treatment, administrative social security records show emerging positive effects on days worked, contract stability, and full-time employment, especially in the digital-skills group. We also find evidence of a psychological awareness effect: low-engagement participants reported lower self-assessed transversal skills, possibly reflecting a shift in self-perception. Our findings highlight the potential of multidimensional, personalized activation strategies to foster formalization and digital inclusion among low-income populations.
Keywords: I32; I38; E24; C93; 330; social inclusion; active labor market policies; randomized controlled trial